Investor Attention and Technology Salience: Does Personal Data Related Innovation Boost Firm Value? - Heli Koski; Juha Luukkonen (The Research Institute of the Finnish Economy (ETLA), 2018)
This paper empirically analyzes how markets value personal data related innovation in four prominent domains, in which firms' potential to exploit value from data is identified to be considerable: finance, health, location-based services and artificial intelligence. We link the innovation economics literature to psychology-grounded financial economics theories of investor attention and salience theory. Our data from 117 large technology companies active in the ICT sector from the years 2007–2014 suggest that firms' personal data related innovations and knowledge stocks in technology domains of location-based services and artificial intelligence contributed substantially to firm value. The premiums gained from personal data related innovation were particularly significant for data giants holding knowledge stocks in the location-based service domain. Our empirical results indicate that a strong positive relationship between personal data related knowledge stocks of the location-based services domain and firm value relates primarily to investor attention intensified during periods of media hype. Our data provide new insights into the market valuation of intangible assets: investors seem to overweight more salient right tails of firms' knowledge stocks of emerging technologies while neglecting salient left tails.
Keywords: D22; G41; L2; O3; 330; Firm value; Innovation; Personal data; Investor attention; Saliency theory; Technology salience